2017
DOI: 10.1093/neuonc/nox018
|View full text |Cite
|
Sign up to set email alerts
|

Frequent AKT1E17K mutations in skull base meningiomas are associated with mTOR and ERK1/2 activation and reduced time to tumor recurrence

Abstract: AKT1E17K mutation is frequent in skull base meningiomas, results in activation of the mTOR and ERK1/2 signaling pathways, and has negative impact on tumor recurrence. Patients with skull base meningiomas with AKT1E17K mutation might benefit from additional treatment targeting the mTOR pathway. Generally, the PI3K-Akt-mTOR axis might be a potential target for kinase inhibitors in these tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 26 publications
2
61
2
1
Order By: Relevance
“…It has been shown that the PI3K signaling pathway is closely related to tumor formation, therefore, the expression of related proteins was analyzed with Western blot assay . These results showed that phospo‐AKT and phospo‐mTOR levels were significantly decreased in UNBS5162 treated A549 cells ( P < 0.05).…”
Section: Resultsmentioning
confidence: 97%
“…It has been shown that the PI3K signaling pathway is closely related to tumor formation, therefore, the expression of related proteins was analyzed with Western blot assay . These results showed that phospo‐AKT and phospo‐mTOR levels were significantly decreased in UNBS5162 treated A549 cells ( P < 0.05).…”
Section: Resultsmentioning
confidence: 97%
“…To the best of our knowledge, four previous studies investigated and demonstrated p-mTOR Ser2448 immunoexpression in meningiomas of all histological grades. [18][19][20][21] According to those, [19][20][21] p-mTOR Ser2448 is expressed in grades I, II and III meningiomas, with no significant difference according to tumor grade. One study, including meningiomas of all grades, found no correlation between p-mTOR expression and the patients' overall survival.…”
Section: Discussionmentioning
confidence: 97%
“…Yesilöz and colleagues previously found that p‐mTOR Ser2448 is present in half of skull base meningiomas and that its expression is significantly associated with AKT1 mutation, which is more frequent in tumors located in the anterior/middle skull base. However, our findings show that p‐mTOR Ser2448 immuno‐expression is not exclusive of skull base meningiomas, but it can also be observed in tumors at the convexity or in sagittal meningiomas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations